Patient Performance of Care Tasks During Acute Hospitalisation: A Scoping Review. - Kurtz, Chava; Tonkikh, Orly; Spitzer, Sivan; Shadmi, Efrat (Journal of Clinical Nursing (John Wiley & Sons, Inc.), 2025)
Background: Patient self‐care is established as improving outcomes, yet acute care in hospitals is provided such that patients tend to be passive recipients of care. Little is known about the extent and type of patient participation in treatment care tasks in acute hospital settings. Aims: To map and synthesise available literature on self‐performance of care tasks in acute hospital settings. Design: A scoping review was conducted guided by JBI methodology. Methods: A literature search was conducted in July 2021 and updated in March 2024 across five databases: Scopus, PubMed, CINAHL, Embase and Web of Science. Studies were screened using predefined eligibility criteria. Full‐text screening and data extraction were performed independently by two researchers. Data were collected using a template specifically designed for this review. Reporting followed the PRISMA‐ScR guideline. Results: Of the 31,361 articles identified, 35 were included. Most of the articles were experimental (n = 20) and conducted in Europe (n = 13), North America (n = 10) and Australia (n = 3). Studies were classified according to investigation of the performance of care tasks (n = 6) or of the outcomes of the performance of the self‐care task (n = 29). Most tasks performed involved self‐administration of medication (n = 31), only 4 articles referred to other care tasks. Most articles focused on acute tasks (n = 18), while 15 articles referred to chronic care tasks. Ostomy self‐care (n = 2) was a separate category, being an acute task that continued into chronic self‐care. Conclusion: Performance of care tasks by patients in acute care settings are predominantly related to chronic and pain medication administration. Implications for Care: Patient preferences and competency to self‐perform care tasks during hospitalisation should be assessed and monitored and supported accordingly. Utilising hospitalisation time to observe and assess self‐care practices could provide additional teaching opportunities to patient self‐care and improve overall care continuity. Reporting Method: The PRISMA‐ScR guideline was followed. Patient or Public Contribution: No Patient or Public Contribution. Trial and Protocol Registration: This review was registered on Open Science Framework before running the final search: (https://doi.org/10.17605/OSF.IO/D8KS2).